Breakfast in the rainforest : a visit with mountain gorillas - Sobol, Richard (Traveling photographer, 2008)
Powerful but shy, the African mountain gorilla struggles for survival in the rainforests of Uganda<U+2019>s national parks. Through extraordinary images and a compelling text, wildlife photographer Richard Sobol leads us on an arduous journey to the gorillas<U+2019> hidden habitats and offers a hushed, close-up look at the gentle giants as they nibble on leaves for their morning meal. Striking photographs of the little-seen ritual remind readers of the wonders of this dwindling species, while a first-person narrative describes the photographer<U+2019>s journey <U+2014> and tells of efforts being made to preserve these magnificent creatures. Back matter includes mountain gorilla facts, online resources, a glossary, and an afterword by Leonardo DiCaprio.